Zoonotic onchocerciasis in Hiroshima, Japan, and molecular analysis of a paraffin section of the agent for a reliable identification - Fukuda M.; Otsuka Y.; Uni S.; Boda T.; Daisaku H.; Hasegawa H.; Takaoka H.; Bain O. (Parasite, 2011)
Japan is a country of high specific diversity of Onchocerca with eight species, the adults of two not yet known. Onchocerca dewittei japonica, a common filarial parasite of wild boar, had been proved to be the agent of five zoonotic onchocerciasis in Kyushu island with morphological and molecular studies. The sixth case, at Hiroshima in the main island, was identified to the same Onchocerca species, based on adult characters observed on histological sections. To consolidate the identification, mitochondrial cytochrome c oxidase subunit 1 (CO1) gene analysis was attempted with the formalin-fixed, paraffin-embedded parasite specimen. The sequence (196 bp) of a CO1 gene fragment of the parasite successfully PCR-amplified agreed well with those of O. dewittei japonica registered in GenBank, confirming the morphological identification. Moreover a comparison with the CO1 gene sequences of six other Onchocerca species in GenBank excluded the possibility that Onchocerca sp. from wild boar and Onchocerca sp. type A from cattle in Japan, were the causative agents in this case. Mitochondrial DNA analysis proved to be a valuable tool to support the morphological method for the discrimination of zoonotic Onchocerca species in a histological specimen.